Pemanfaatan Bakteri Termofilik Penghasil Amilase Pada Berbagai Pati - Nin Suharti; Geminsah Putra (Poltekkes Kemenkes Medan, 2023)
Indonesia is a country that produces a lot of starchy materials such as cassava, sago, corn and others. Indonesia has the potential to develop an enzyme-producing industry, especially amylase. The utilization of starchy materials which so far has not been maximized and is still limited to conventional methods can be increased by enzymatic development processes. This will increase its economic value and at the same time increase state income. One of the enzymes that is currently very widely used in the food and beverage industry is amylase. Nin Suharti and Geminsyah Putra 2021 have succeeded in isolating and identifying thermophilic bacteria from the sidedust hot springs of North Sumatra. The advantage of thermophilic bacteria is that they can produce enzymes that are resistant to high temperatures / thermostable enzymes. These enzymes are able to survive and are active at high temperatures. Such properties are highly needed by enzyme-based industries. The use of enzymes that can withstand high temperatures in the field of biotechnology can reduce operating costs and increase reaction speed, this study uses various types of starch including potatoes, cassava and corn as suitable and easily available carbon sources for the production of amylase enzymes. Bacteria in the media with potato starch added can produce the highest amylase enzyme from the three treatments of 65 U/L. For bacteria added with corn starch, the result was 50 U/L of amylase enzyme. Meanwhile, the lowest of the three treatments was media with added sweet potato starch with a content of 39 U/L. The isolates generally had a round shape, jagged edges, grooved, and smooth, white colonies, microscopic bacilli-shaped, endospores and motile, positive for catalase, gelatin and citrate tests. With Gram staining, it generally shows a positive Gram reaction.